Catalytic Transformation of Triglycerides to Biodiesel with SiO2-SO3 H and Quaternary Ammonium Salts in Toluene or DMSO - Barbosa, Sandro L.; Rocha, Adeline C. Pereira; Nelson, David Lee; de Freitas, Milton S.; Mestre, Antônio A. P. Fulgêncio; Klein, Stanlei I. [UNESP]; Clososki, Giuliano C.; Caires, Franco J.; Flumignan, Danilo L. [UNESP]; Dos Santos, Letícia Karen [UNESP]; Wentz, Alexandre P.; Pasa, Vânya M. Duarte; et al. (MDPI, 2022)
SiO2-SO3 H, with a surface area of 115 m2·g−1, pore volumes of 0.38 cm3·g−1 and 1.32 mmol H+ /g, was used as a transesterification catalyst. Triglycerides of waste cooking oil reacted with methanol in refluxing toluene to yield mixtures of diglycerides, monoglycerides and fatty acid methyl esters (FAMEs) in the presence of 20% (w/w) catalyst/oil using the hydrophilic sulfonated silica (SiO2-SO3 H) catalyst alone or with the addition of 10% (w/w) co-catalyst/oil [(Bun 4N)(BF4) or Aliquat 336]. The addition of the ammonium salts to the catalyst lead to a decrease in the amounts of diglycerides in the products, but the concentrations of monoglycerides increased. Mixtures of (Bun 4N)(BF4)/catalyst were superior to catalyst alone or Aliquat 336/catalyst for promoting the production of mixtures with high concentrations of FAMEs. The same experiments were repeated using DMSO as the solvent. The use of the more polar solvent resulted in excellent conversion of the triglycerides to FAME esters with all three-catalyst media. A simplified mechanism is presented to account for the experimental results.
Keywords: Aliquat 336; Fatty acid methyl esters; Hydrophilic sulfonated silica catalyst; Tetrabutylammonium tetrafluoroborate; Transesterification